2021
DOI: 10.1155/2021/4186102
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Matrine on Collagen-Induced Arthritis Rats and Its Regulatory Effect on RANKL and OPG Expression

Abstract: Objective. To investigate the effect of matrine on rats with collagen-induced arthritis (CIA) and its regulatory effect on receptor activator of nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) expression. Methods. Wistar rats ( n = 6 ) and CIA rats ( n = 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The ratio of RANKL/OPG is usually used in reflecting the ability of osteoclastogenesis and the degree of OC-mediated bone resorption. A high RANKL/OPG ratio reflects an increase in bone loss, while a low ratio reflects a decrease in bone loss [ 64 ]. OBs also secrete a mass of TGF- β 1 considered as the core cytokine that dominate bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of RANKL/OPG is usually used in reflecting the ability of osteoclastogenesis and the degree of OC-mediated bone resorption. A high RANKL/OPG ratio reflects an increase in bone loss, while a low ratio reflects a decrease in bone loss [ 64 ]. OBs also secrete a mass of TGF- β 1 considered as the core cytokine that dominate bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Same as the effect of OBs on OCs, OCs can influence the function of OBs through regulating cytokines such as TGF- β 1, BMP-2, IGF-1, and Atp6v0d2. TGF- β 1 is released from the bone matrix due to OC-mediated bone resorption and is activated in acidic environment resulting from activated OCs [ 64 ]. TGF- β 1 promotes BM-MSC proliferation, migration, and differentiation into OBs through Smad2/3 pathway and promotes OB proliferation and matrix maturation [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug MTX is commonly used in the treatment of RA. The level of RANKL was decreased whereas the OPG level was improved after MTX treatment (Li et al, 2021). Phenolic acids play an important role in the inhibition of osteoclastogenesis, thus preventing bone tissue loss.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 53 observed in in vitro experiments that matrine inhibits the expression of TRAF6, interferes with its binding to receptor activator of nuclear factor‐κB (RANK), and inhibits the activation of NF‐κB, c‐Fos, and NFATc1 in a dose‐dependent manner, ultimately causing osteoclast activation disorders. In their subsequent study, Li et al 54 provided evidence that matrine alleviates bone degradation and enhances the expression of osteoprotegerin and the osteoprotegerin/RANK ligand ratio, while suppressing the expression of RANK ligand in rats with CIA. Both studies indicated that matrine inhibits the NF‐κB pathway.…”
Section: Signaling Pathways Involved In the Therapeutic Effect Of Mat...mentioning
confidence: 99%